2011
DOI: 10.1038/eye.2011.61
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of supporting role of a foldable capsular vitreous body with magnetic resonance imaging in the treatment of severe retinal detachment in human eyes

Abstract: Purpose To determine the supporting role of a novel foldable capsular vitreous body (FCVB) with magnetic resonance imaging (MRI) in the treatment of severe retinal detachment in human eyes. Methods The study examined nine eyes of nine patients. Among the nine eyes, five had suffered penetrating injuries while four had suffered contusions of the eyeball involving large defects of the retina or choroids. A standard three-port pars plana vitrectomy was performed, FCVB was triple-folded and sent into the vitreous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…42 Therefore, FCVB results also may have implications in the treatment of important retinal diseases that need drug and vitreous substitutes, such as age-related macular degeneration, proliferative vitreoretinopathy, and proliferative diabetic retinopathy. This work, along with our other reports regarding the FCVB, [21][22][23][24][25][26][27][28][29][30]42 give an example of how to make the product from bench to bedside, including idea, craft, animal model, producing standard, technical reports from government, clinical trails (exploratory, multiple centers), and marketing. Based on this study, we will apply for a new clinical trial to test the combined function of FCVB.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…42 Therefore, FCVB results also may have implications in the treatment of important retinal diseases that need drug and vitreous substitutes, such as age-related macular degeneration, proliferative vitreoretinopathy, and proliferative diabetic retinopathy. This work, along with our other reports regarding the FCVB, [21][22][23][24][25][26][27][28][29][30]42 give an example of how to make the product from bench to bedside, including idea, craft, animal model, producing standard, technical reports from government, clinical trails (exploratory, multiple centers), and marketing. Based on this study, we will apply for a new clinical trial to test the combined function of FCVB.…”
Section: Discussionmentioning
confidence: 94%
“…[28][29][30] An exploratory clinical trial conducted at Zhongshan Ophthalmic Center in China suggested that an FCVB was a flexible, effective, and safe vitreous substitute over a 3-month implantation period in 11 human eyes 28 and over a 12-month implantation in 3 human eyes. 30 Currently, multiple center clinical trials are in progress to ascertain FCVB efficacy and safety as a novel vitreous substitute in nine hospitals in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also used magnetic resonance imaging to monitor the support of the FCVB and found that FCVB can fully fill the vitreous cavity. 23 Therefore, FCVB provides us with a new therapeutic theory and product for severe RD.…”
Section: Discussionmentioning
confidence: 99%
“…Attachment of the macula at presentation was associated with an improved visual outcome [9, 10]. Developing endophthalmitis conferred an inferior visual outcome in one study [18] but was not shown to have the same effect in another [14]. Recurrent retinal detachment predicted a worse visual outcome [10], as did total RD on presentation, retention of silicone oil in the eye, and development of PVR [14].…”
Section: Discussionmentioning
confidence: 99%